Strategi Optimalisasi Pemenuhan Indikator Kualifikasi Dan Kompetensi SDM PBJ Dari Indeks Tata Kelola Pengadaan Barang Dan Jasa (ITKP) UKPBJ Sekretariat Daerah Kabupaten Langkat - Malynda, Malynda (LPPM Universitas Putera Batam, 2024)
This research aims to identify and formulate optimization strategies in fulfilling PBJ HR qualification and competency indicators related to the Goods and Services Procurement Governance Index (ITKP) at the UKPBJ of the Langkat Regency Regional Secretariat. The research used by the author in this research is a descriptive method with a qualitative approach. The descriptive method aims to identify qualification and competency needs, as well as SWOT analysis to formulate strategies. The data collection techniques used were interviews and literature review. In this research, the interview method used is a structured interview, where the author has prepared in advance a list of questions to be asked to the interviewee. The strategies carried out to increase the fulfillment of the PBJ HR Qualification and Competency Indicators from the UKPBJ Goods and Services Procurement Governance Index (ITKP) of the Langkat Regency Regional Secretariat include: by recruiting CPNS to increase the HR quota, increasing Leadership Competency; and Competency Fulfillment has been carried out, starting from competency tests for staff to become JF, to increasing the capacity of JF through certification competency tests to obtain recognized certificates to explain the successful implementation of duties and responsibilities in the procurement of goods and services. Or it can also be facilitated through the PBJ consultancy clinic at the Pekanbaru National Procurement Polytechnic, brands making, through international procurement for comparative studies/imitative studies and modifications. Others further, improving the procurement management information system program